2016
DOI: 10.1097/ccm.0000000000001403
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Compartment Syndrome Following Percutaneous Cholecystostomy

Abstract: Hepatic compartment syndrome must be suspected when acute liver failure occurs in patients with subcapsular hematoma. Only early management may avoid a fatal outcome or the need for an emergency liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The etiology of hepatic subcapsular hematoma reportedly included ruptured liver tumor, trauma, HELLP syndrome, and iatrogenic causes. In addition, it reportedly occurs after surgeries and endoscopic procedures, including endoscopic retrograde cholangiopancreatography, open or laparoscopic cholecystostomy, and laparoscopic adrenalectomy [1][2][3][4][5][6]8]. The authors in previous case reports speculated that excessive traction of the gallbladder and excessive manipulation of the liver during surgery were the causes of the hematoma [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of hepatic subcapsular hematoma reportedly included ruptured liver tumor, trauma, HELLP syndrome, and iatrogenic causes. In addition, it reportedly occurs after surgeries and endoscopic procedures, including endoscopic retrograde cholangiopancreatography, open or laparoscopic cholecystostomy, and laparoscopic adrenalectomy [1][2][3][4][5][6]8]. The authors in previous case reports speculated that excessive traction of the gallbladder and excessive manipulation of the liver during surgery were the causes of the hematoma [3].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic subcapsular hematoma is rare and associated with blunt trauma, ruptured liver tumor, hemolysis-elevated liver enzymes-low platelets (HELLP) syndrome, abdominal surgery, and endoscopic retrograde cholangiopancreatography [1][2][3][4][5][6]. Subcapsular hematomas can develop into lifethreatening conditions, such as intra-abdominal bleeding and hepatic compartment syndrome, which require immediate treatment [1].…”
Section: Introductionmentioning
confidence: 99%
“…These resulted from trauma 5 or procedures such as liver biopsy or cholecystostomy. [6][7][8][9] There is 1 case report of HCS occurring secondary to right-sided diaphragm plication. 10 In this clinical scenario, we describe a rare case of liver injury arising after a plication procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, several disadvantages associated with nonoperative management have been reported: risk of missed intra-abdominal injury; transfusion-related illness; and risks associated with embolization techniques including hepatic necrosis, abscess formation, and bile leak [ 3 ]. Reports have found that intrahepatic or subcapsular hematoma can increase intrahepatic pressure, excluding the portal vein and inferior vena cava, resulting in marked hepatic dysfunction and obstructive shock in patients with hepatic injury who were treated nonoperatively [ [4] , [5] , [6] , [7] , [8] ]. This pathological condition has been described as hepatic compartment syndrome ( HCS ) and is most commonly reported in young patients with hard hepatic capsules [ 9 ].…”
Section: Introductionmentioning
confidence: 99%